Finite Element Modeling Of Ballistic Penetration into Fabric Armor - Talebi, Hossein (2006)
The goal of this work is to analyze the ballistic performance of plain woven fabric used in soft armor systems using a detailed finite element analysis at yarn level. As more complex materials systems are introduced in engineering practice, the design engineer faces the dilemma of utilizing homogenization techniques or detailed numerical models. The latter offers a number of advantages, such as the ability to introduce separate constitutive laws and failure criteria for each phase, at the expense of computation cost. This is particularly important in ballistic performance of the soft armor where the projectile-fabric interaction and failure modes are complicated and can not be realized in other approaches. An automatic geometry generation algorithm for textile is developed that can generate complex fabric geometries spanning several unit cells. This program (named DYNTEX) based on the mentioned algorithm is designed using MATLAB code. A commercial finite element code named LS-DYNA is used as the solver and DYNTEX program is then extended to do the pre-processing for LS-DYNA. Four types of projectile shapes were chosen which consist of spherical, blunt, conical, hemi-spherical and a conically cylindrical military sized bullet. An orthotropic material with von-Mises stress at failure of 2.7GPa was chosen for material behavior of yarns. Since projectiles did not have considerable deformation, they assumed as rigid bodies. Furthermore a general surface to surface contact was selected for the contact between the yarns and projectile-fabric. Initial conditions and results of experimentations were extracted from literature to validate the simulation results for different projectile shapes. To verify the mesh built by DYNTEX program a relatively low velocity impact simulation performed in oblique angle. Then convergence analysis is then carried out by changing the mesh density of fabric target and it was shown primary mesh density was fine enough to start the remaining simulations. Finite element models of fabric impact were made with initial conditions extracted from literature and simulations were performed. The results of simulations showed close agreement with experimental tests. Moreover several parameters which affect the energy absorption of fabric were studied. These parameters were friction, boundary conditions, projectile nose diameter and projectile nose angle. The mentioned parameters were studied with respect to several projectile nose shapes and boundary conditions.